The Coulomb interaction between pion wavepackets: the π+ - π- puzzle - Merlitz, Holger; Pelte, Dietrich (Journal of physics. G, Nuclear and particle physics, 1999)
The time-dependent Schrödinger equation for ##IMG## [http://ej.iop.org/icons/common/pippim.gif] pi+-pi- pairs, which are emitted from the interaction zone in relativistic nuclear collisions, is solved using wavepacket states. It is shown that the Coulomb enhancement in the momentum correlation function of such pairs is smaller than obtained in earlier calculations based on Coulomb distorted plane waves. These results suggest that the experimentally observed positive correlation signal cannot be caused by the Coulomb interaction between pions emitted from the interaction zone. But other processes which involve long-living resonances and pions emitted with a large coherence length could provide a possible explanation for the observed signal.
Im Titel ist "pi" als griechischer Buchstabe dargestellt
Im Titel ist "+" und "-" hochgestellt
Gesehen am 23.02.2018